Role of Halides in Extraction of Metals - Shamsuddin M. (My University, 2025)
The halide route in metal extraction has been found to be economically suitable for the large-scale production of many reactive and rare metals, for example, beryllium, calcium, magnesium, niobium, sodium, tantalum, thorium, titanium, uranium, vanadium, and zirconium. The refractory oxides of some of these metals can be reduced with carbon only at high temperatures. In most cases carbides are formed, decomposition of which is difficult. During reduction many of these metals dissolve large amounts of oxygen (even in solid state), which cannot be easily removed. For effective removal of oxygen, these oxides have to be reduced with calcium. However, whether reduction reaction is carried out between liquid calcium and solid/liquid oxide, separation of the solid CaO (deoxidation product) is often troublesome. Reduction of fluoride/chloride by calcium or magnesium is a much easier operation where slag/metal separation is facilitated by the formation of either molten metal or molten slag. For example, reduction of uranium tetra fluoride by calcium produces liquid uranium whereas molten magnesium chloride slag is obtained when gaseous titanium tetra chloride or zirconium tetra chloride is reduced with magnesium. Generally, minerals do not occur as halides (fluoride, chloride, bromide, or iodide); however, conversion of stable oxides of rare/reactive metals (viz. Be, Ti, Zr, U, and Th) into halides offers an alternative route for metal extraction. As halides of reactive metals are less stable than their oxides, they can be easily produced by metallothermic reduction. Carbon may be used as a reducing agent to remove oxygen during chlorination of oxides of reactive metals like titanium, zirconium, and magnesium whereas UO2 and ThO2 are converted to fluorides by hydrofluorination. Beryl (3BeO·Al2O3·6SiO2) is subjected to complex fluoride processing to convert beryllium value into water-soluble sodium beryllium fluoride. Subsequently, the leach liquor is processed to obtain BeF2. These chlorides and fluorides are reduced with magnesium or calcium for metal production. © 2021, The Minerals, Metals & Materials Society.